Assessing the Science Learning Assessment (SLA) Instrument in Greek Early Childhood Education Using the Item Response Theory Framework - Grammatikopoulos, Vasilis; Tsigilis, Nikolaos; Gregoriadis, Athanasios (Frontiers in Education, 2019)
Studies revealed that science learning in early childhood is associated with primary and secondary school readiness, improved causal reasoning, increased interest in science in later life, and with long-term effects on academic achievement. Thus, having valid and reliable instruments to assess children’s science learning becomes critical in early childhood education (ECE). The main goal of the current study was to examine the psychometric properties of the Greek version of the Science Learning Assessment (SLA), an instrument developed in the USA to assess science learning in ECE. Randomly selected from 53 preschool units in Greece, 528 children were administered with the Greek version of the SLA. Advanced statistical methods (CFA, IRT framework) were employed to analyse the data and the results showed that the Greek version of the SLA displayed acceptable psychometric properties. Therefore, it can be argued that the Greek version of the SLA is a valid and reliable scale for assessing children’s science knowledge in ECE, capturing universal concepts of science knowledge children in early childhood.